Problem solving approach in health education - Guerra, Pacita M. 1928- (s.n.], 1969)
The main purpose of this paper is to present ways by which the problem-solving method can be applied in teaching health education. This paper attempts to provide the teachers a guide in the effective use of problem solving as a method in health education, and inspire and encourage teachers in experimenting on the effective use of other methods by developing guidelines such as the ones shown in this study.